Comparison of maxillofacial growth characteristics in patients with and without cleft lip and palate - Rohit Khanna; Tripti Tikku; Sneh Lata Verma; Geeta Verma; Saumil Dwivedi (Wolters Kluwer Medknow Publications, 2020)
Introduction: The neurotropic growth precedes the somatic growth, in the craniofacial region, any lag or disturbance in the development of cervical vertebrae may attribute to the development of craniofacial cleft. Objective: The aim of this study is to evaluate the developmental relationship of cervical vertebrae and maxillofacial morphology in complete cleft lip and palate patients (untreated and surgically treated) and noncleft patients based on the parameters on lateral cephalograms. Materials and Methods: One hundred and sixty patients were first divided into two groups, Group I patients (6-12 years) and Group II patients (12-18 years). These groups were further subdivided into three subgroups, i.e., noncleft or normal patients, untreated cleft group, and surgically treated cleft group patients. Thirteen angular and 19 linear parameters taken on digital lateral cephalogram were analyzed and discussed to evaluate and compare the growth status and craniofacial morphology. Results: There was no significant delay in skeletal maturity noted in cleft patients when they were compared with their normal counterparts. Cranial base length and the cranial base angle were insignificantly reduced in cleft groups, whereas the maxilla in surgically treated patients was found to be significantly shorter along with retroposition and clockwise rotation with respect to cranial base. Mandible was shorter in length and posteriorly positioned with respect to cranial base with downward and backward rotation in surgically untreated and treated cleft patients, but the difference was statistically nonsignificant. Marked differences in maxillo-mandibular relationship were seen in surgically treated patients suggestive of the establishment of Class III jaw relation in those patients. Conclusion: The iatrogenic repercussion of surgery on cleft patients has a significant restraining effect on maxilla, mandible, and maxillo-mandibular relationship and morbidity do not play a significant role in delaying skeletal maturity.